THE CASE FOR ROMANIAN AUTOFICTION. LOVE & ANXIETY IN THE NEOLIBERAL WORLD IN RADU VANCU’S AND SAȘA ZARE’S NOVELS - TOHĂTAN, Horațiu (Studia Universitatis Babeș-Bolyai Philologia, 2025)
The Case for Romanian Autofiction. Love & Anxiety in the Neoliberal World in Radu Vancu’s and Sașa Zare’s Novels. The origins of autofiction encapsulate this literary species in a postmodernist ethos. Nevertheless, the 2000s generation of Romanian writers developed an appetency for autofiction that exposed the questioning potentialities of self-narration towards the contemporary neoliberal status-quo. Being called a hybridization between metarealism and miserable realism (Mihai Iovănel) or an extension of the neoliberal novel (Adriana Stan), theories highlight its ambiguous, volatile, almost non-specific character. However, in the case of Romanian contemporary literature, two post-2000s novels engage in polemics regarding the way in which individuality, memory and trauma are revisited through autofiction, using metadiscourse, biography, and fictive discourse. Radu Vancu’s Transparența (Transparency) and Sașa Zare’s Dezrădăcinare (Uprooting) are exponential in understanding autofiction’s main strategies of narration. This paper examines how autofiction evolved after the 2000s generation of self-narrators, trying to question how this literary species fits or challenges the neoliberal political context. Being easy to portray a relative cause for autofiction’s focus on individual or social motifs, this paper will dwell into how the self and the interhuman erotic relationships are exposed in the prior mentioned novels. In the second part of the study, an in-depth analysis of Transparența will examine how sensibility, eroticism, and anxiety are handled in an introvert autofictional way (Florina Pîrjol), where the decentralisation of self is dealt with maximalist strategies. Finally, Sașa Zare’s autofictional innovations will portray how the extrovert side evolved in the neoliberal context, proposing a new form of authenticity, where the self and queer eroticism are expressed towards an integrated communitarian audience. REZUMAT. Cazul autoficțiunii românești. Iubire & anxietate în lumea neoliberală în romanele lui Radu Vancu și al Sașei Zare. Originile autoficțiunii prezintă această specie literară ca parte a unui ethos postmodernist. Cu toate acestea, generația 2000-istă de scriitori români a dezvoltat o apetență pentru autoficțiune care a pus la îndoială potențialitățile narațiunii de sine față de un status-quo contemporan, neoliberal. Numită drept o hibridizare între metarealism și realism mizerabilist (Mihai Iovănel) sau o extensie a romanului neoliberal (Adriana Stan), teoriile sale emergente au punctat caracterul ambiguu, volatil și lipsit de specificitate al autoficțiunii. Pe de altă parte, in cazul literaturii române contemporane, două romane post-2000-iste construiesc o polemică referitoare la modul în care individualitate, memoria și trauma sunt revizitate prin autoficțiune, folosind metadiscurs, discurs biografic și fictiv. Transparența de Radu Vancu și Dezrădăcinare de Sașa Zare sunt exponențiale pentru înțelegerea strategiilor autoficționare de narare. Această lucrare examinează evoluția autoficțiunii după generația 2000-istă, încercând să chestioneze modul în care această specie literară se mulează ori provoacă cadrul politic neoliberal. Fiind ușor de construit o cauză relativă pentru care autoficțiunea se concentrează pe motive individualiste sau sociale, această lucrare va investiga cum sinele și relațiile erotice interumane sunt expuse în romanele menționate. În cea de-a doua parte a studiului meu, o analiză mai îndeaproape a romanului Transparența va examina cum sensibilitatea, eroticul și anxietatea sunt jonglate la nivel introvertit (Florina Pîrjol), acolo unde descentralizarea sinelui este redată prin strategii manieriste. În sfârșit, inovațiile autoficționale ale Sașei Zare vor portretiza cum latura extrovertită a evoluat într-un cadru neoliberal, propunând o nouă formă de autenticism, unde sinele și erotica queer sunt exprimate către un public integrat narativ. Cuvinte-cheie: autoficțiune, roman neoliberal, ficțiune biografică, roman post-2000-ist, erotică, autobiografie. Article history: Received 24 June 2025; Revised 11 August 2025; Accepted 31 August 2025; Available online 24 September 2025; Available print 30 September 2025